Peningkatan Keterampilan Berpikir Kritis Siswa Melalui Model Pembelajaran Problem Based Learning Pada Mata Pelajaran PAI Kelas 4 SDN Putat Jaya 1/ 377 Surabaya - Siti Umiyati; Desy Rahmayanti Khumairo (Jurnal Pendidikan Agama Islam Miazhar, 2024)
Based on the phenomenon observed at SDN Putat Jaya 1/377 Surabaya, student learning outcomes remain suboptimal, with 57% of students failing to meet the required standards and in need of improvement. Essentially, various learning activities carried out by teachers thus far have been related to cognitive improvement but have not specifically focused on developing critical thinking skills. The implementation of the Problem-Based Learning model in Islamic Education (PAI) has significantly improved students' critical thinking abilities, particularly in Grade 4, with an increase in student achievement of 42.86%. In Cycle II, students' critical thinking skills reached a score of 88, exceeding the Action Research performance indicator of 85%. Students' responses to the learning process were also very positive, with 97% of students feeling comfortable and more engaged with the Problem-Based Learning approach. Additionally, students' academic achievement improved by 9 points, from 76 to 85, and was considered satisfactory as 89% of the students surpassed the Minimum Competency Criteria (KKM) score of 85 based on the average test results. The implementation of learning procedures using the Problem-Based Learning model ran smoothly and was in line with the Lesson Plan (RPP) that had been prepared.